2022
DOI: 10.1002/advs.202104134
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Reprogramming Amino Acid Polymer as an Immunosurveillance Activator and Leukemia Targeting Drug Carrier for T‐Cell Acute Lymphoblastic Leukemia

Abstract: Compromised immunosurveillance leads to chemotherapy resistance and disease relapse of hematological malignancies. Amino acid metabolism regulates immune responses and cancer; however, a druggable amino acid metabolite to enhance antitumor immunosurveillance and improve leukemia targeting‐therapy efficacy remains unexplored. Here, an L‐phenylalanine polymer, Metabolic Reprogramming Immunosurveillance Activation Nanomedicine (MRIAN), is invented to effectively target bone marrow (BM) and activate the immune sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…In addition, pharmacological blockade of FATP2 expression in MDSCs reduced lipid accumulation, decreased ROS levels, attenuated the immunosuppressive activity of MDSCs, and reduced PD-L1 expression on immune cells, thereby enhancing the effect of tumor immunotherapy [ 136 ]. A recent study found that metabolic reprogramming of the immunosurveillance-activating nanodrug-assembled doxorubicin (MRIAN-Dox) inhibited M2-type pyruvate kinase (PKM2) activity and reduced ROS levels in MDSCs in a T-cell acute lymphoblastic leukemia (T-ALL) mouse model, thereby interfering with their immunosuppressive function and increasing their differentiation to normal bone marrow cells [ 137 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pharmacological blockade of FATP2 expression in MDSCs reduced lipid accumulation, decreased ROS levels, attenuated the immunosuppressive activity of MDSCs, and reduced PD-L1 expression on immune cells, thereby enhancing the effect of tumor immunotherapy [ 136 ]. A recent study found that metabolic reprogramming of the immunosurveillance-activating nanodrug-assembled doxorubicin (MRIAN-Dox) inhibited M2-type pyruvate kinase (PKM2) activity and reduced ROS levels in MDSCs in a T-cell acute lymphoblastic leukemia (T-ALL) mouse model, thereby interfering with their immunosuppressive function and increasing their differentiation to normal bone marrow cells [ 137 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also demonstrated an enhanced cellular uptake of MRIAN in T-ALL cells and MDSC compared to normal hematopoietic cells and progenitors. MRIAN assembled to doxorubicin (MRIAN-Dox) demonstrated an enhanced anti-tumor efficacy and reduced toxicity profile (including cardiotoxicity and myeloablation side effects) in T-ALL mice; indicating its therapeutic potential as metabolic modifier to target MDSC ( 77 ).…”
Section: Therapeutic Approaches To Target Mdsc In Hematological Cancersmentioning
confidence: 99%
“…[7,8] To overcome these limitations, polymer-based nanomedicines have been developed using new materials. [9][10][11] Levan is a polysaccharide comprising a β-D-fructose polymer wherein the fructose rings are linked via β-glycosidic linkages. [12] The amphiphilic properties of levan enable micelles to be fabricated in aqueous solutions through self-assembly.…”
Section: Introductionmentioning
confidence: 99%